Strengthening the Circle: An International Review of Government Domestic Violence Prevention Plans and Inclusion of Indigenous Peoples - Fotheringham, Sarah (Violence against women, 2021)
This study describes the level of government commitment in preventing domestic violence (DV) toward Indigenous women in countries of the Global North. Seventy-two government-endorsed DV prevention plans across 11 countries were analyzed. While more than half of the plans acknowledged Indigenous peoples, the main discourse reinforced a Western DV paradigm, reproduced negative stereotypes, and ignored systemic factors. Little consideration for intersectionality, the impact of colonization, or Indigenous worldviews was evident. Targeted prevention strategies were found but were disjointed and culturally inappropriate. Taken together, these findings suggest minimal government commitment and absence of cultural understanding regarding DV in Indigenous communities.